Molecular characterization of Beauveria isolates from Punjab based on ITS Region - BANTA, GEETIKA; JINDAL, VIKAS (The Indian Journal of Agricultural Sciences, 2019)
Three local isolates of Beauveria (BbR1, BbR2 and BbR3), isolated from Punjab soils along with one standard strain MTCC 2028 (BbM1) were selected for molecular identification. All the isolates showed maximum growth on potato dextrose agar (PDA) for an incubation period of seven days at 28±2°C. Morphologically the shape of colonies was round, lightly raised with white powdery surface and smooth walled hyphae. The mycelia showed white powdery translucent radial growth. Molecular characterization was done based on internal transcribed spacer (ITS) region, a fungal barcoding region for species level identification. The ITS region amplified by PCR with specific primers resulted in 603bp amplicon in all examined Beauveria isolates. The BLAST analysis showed that amplified gene has 99-100% homology with B.bassiana thus confirming all isolates as B.bassiana. The phylogenetic tree exhibited no sequence diversity among Punjab isolates. However, Punjab isolates showed genetic variation of 0.63–1.47% from other Indian isolates based on ITS region. The phylogenetic tree developed, including isolates from other countries, resulted in two main groups.The first group includes all the three local isolates of Punjab, one isolate from Chandigarh, standard BbM1 and 13 from other countries. The second group wasformed by 10 isolates from different states of India and 6 from other countries. The analyses indicated inter and intraspecific variations among B. bassiana isolates associated with diverse geographical origins.